Physical and Biogeochemical Controls of the Phytoplankton Blooms in North Western Mediterranean Sea: A Multiplatform Approach Over a Complete Annual Cycle (2012–2013 DEWEX Experiment). Issue 12 (18th December 2017) - Mayot, Nicolas; D'Ortenzio, Fabrizio; Taillandier, Vincent; Prieur, Louis; de Fommervault, Orens Pasqueron; Claustre, Hervé; Bosse, Anthony; Testor, Pierre; Conan, Pascal
Abstract: The North Western Mediterranean Sea exhibits recurrent and significant autumnal and spring phytoplankton blooms. The existence of these two blooms coincides with typical temperate dynamics. To determine the potential control of physical and biogeochemical factors on these phytoplankton blooms, data from a multiplatform approach (combining ships, Argo and BGC‐Argo floats, and bio‐optical gliders) were analyzed in association with satellite observations in 2012–2013. The satellite framework allowed a simultaneous analysis over the whole annual cycle of in situ observations of mixed layer depth, photosynthetical available radiation, particle backscattering, nutrients (nitrate and silicate), and chlorophyll‐a concentrations. During the year 2012–2013, satellite ocean color observations, confirmed by in situ data, have revealed the existence of two areas (or bioregions) with comparable autumnal blooms but contrasting spring blooms. In both bioregions, the ratio of the euphotic zone (defined as the isolume 0.415 mol photons m −2 d −1, Z0.415 ) and the MLD identified the initiation of the autumnal bloom, as well as the maximal annual increase in [Chl‐a] in spring. In fact, the autumnal phytoplankton bloom might be initiated by mixing of the summer shallowing deep chlorophyll maximum, while the spring restratification (when Z0.415 /MLD ratio became >1) might induce surface phytoplankton production that largely overcomes the losses. Finally, winter deep convection events that took place in one of the bioregions induced higher net accumulation rate of phytoplankton in spring associated with a diatom‐dominated phytoplankton community principally. We suggest that very deep winter MLD lead to an increase in surface silicates availability, which favored the development of diatoms. Key Points: The initiation of the autumnal bloom is linked to the mixing of the shallowing summer DCM Heat fluxes and restratification of the mixed layer control the spring bloom dynamics Deep winter convection events enhance the spring bloom's magnitude by favoring diatoms development